Clinical and laboratory aspect of leptospirosis in humans - Setiawan, I Made (Universa Medicina, 2008)
Leptospirosis is a world-wide zoonotic disease, especially in tropical and subtropical regions. The disease is found in rural and urban areas with poor environmental conditions. The spectrum of human disease ranges from subclinical infection to severe clinical disease with multi-organ failure (Weilâs disease) and high mortality rate, and depends both on the host and the infecting serovar. Leptospirosis may occur either sporadically or in the context of an outbreak and is commonly related to occupational or recreational activities that involve direct or indirect contact with the urine of animal species that are reservoirs of the disease. The disease infects man through contact with contaminated environments or direct contact with carrier animals such as rats, dogs, cattle, pigs, etc. Leptospirosis has clinical symptoms similar to such diseases as dengue, malaria, typhoid, influenza, thus laboratory methods are required for early detection to facilitate appropriate treatment of patients. The diagnosis of leptospirosis should be considered in any patient presenting with an abrupt onset of fever, chills, conjunctival suffusion, headache, myalgia, and jaundice. Suspicion is further increased if there is a history of occupational or recreational exposure to infected animals or to an environment potentially contaminated with animal urine. Treatment commonly consists of administration of antibiotics such as penicillin, ampicillin, amoxicillin, tetracycline and doxycycline. Prevention by immunization is uncommon, as the available vaccines are ineffective in preventing the disease. In general, prevention is by avoiding environmental exposure.